Prognostic Indicator in Severe Acute Pancreatitis - Khanolkar, Dr. Ajay; Khare, Dr. Manish (International Journal of Innovative Research in Medical Science, 2018)
Aim of study: - To assess the utility of each as prognostic indicator in Severe Acute Pancreatitis. Material and Methods: This prospective study entitled “To assess the utility of each as prognostic indicator in Severe Acute Pancreatitis” was carried out on patients hospitalized for acute pancreatitis in the surgery department at Chandulal Chandrakar Memorial Medical College and CM Hospital, Bhilai from March 2015 to October 2017.50 patients with the diagnosis of first attack of acute pancreatitis of both sexes and all age groups were selected for the study. Conclusion:- On the basis of observation and result of the study, it can be safely stated that APACHE II Scoring is quick, safe, reproducible, ongoing and cost effective. It can be done by resident or intelligent nursing staff. Give an idea regarding improving or worsening of patients. APACHE II Scoring system when complimented by high quality CECT abdomen can further refine the results and give an idea of likelihood of patients developing local complication. Thus it can also be used along with CECT abdomen for Risk Stratification of subset of patients who are likely to develop local complication who might need surgical intervention. CECT on 3rd day adds nothing to management. It has a tendency to over predict the regional complication, which are in anyway apart of natural course of history of disease (acute fluid collection). Management decision could not be based on CECT abdomen on 3rd day alone, since it is not needed to make a diagnosis of acute pancreatitis it should be abundant, thus reducing the financial burden of patients and institute. CECT abdomen done after 2nd week in the course of illness along with APACHE II Score and clinical finding are better guide for management and surgical intervention.